Western religious thought - Ausmus, Harry J (Journal of the American Academy of Religion, 1982)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/075-157-295-827-36X tex.type: [object Object]
Keywords: dept.his

Will Herberg, from Right to Right - Ausmus, Harry J. (University of North Carolina Press, 1987)
A study of the life and thought of Will Herberg (1906-1977), a theorist in sociology and religion. A communist in the 1920s-30s, Herberg was identified in the 1950s as a moderate and an advocate of American religious pluralism, and in the 1960s as an anti-communist crusader. On pp. 81-84 shows how, after his abandonment of communism and rediscovery of Judaism, Herberg viewed antisemitism as the inevitable result of the Jew's marginal position in the world and of Judaism's witness to God's message. He contended that Christians who engaged in antisemitism were rebelling against their religion and lapsing into paganism. He condemned Soviet antisemitism and predicted the USSR's adoption of anti-Zionism. He also discussed the reasons for Black antisemitism (pp. 191-194).
Keywords: Biography; Biography; Jewish scholars; Biography; Jews; Herberg; Will; Religion historians; United States; dept.art; faculty_collection

Will Herberg, a bio-bibliography - Ausmus, Harry J. (Greenwood Press, 1986)
Keywords: Bio-bibliography; Religion historians; Biography; Herberg; Will; United States; dept.art; faculty_collection

The Polite Escape: On the Myth of Secularization - Ausmus, Harry J. (Ohio University Press, 1982)
Keywords: 20th century; 20th century; Nihilism (Philosophy); History; History of doctrines; Secularization (Theology); dept.art; faculty_collection

Review of L'ordre du temps - Ausmus, Harry J. (The American Historical Review, 1985)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1985ASN9100005 tex.unique-id: [object Object]
Keywords: dept.his

Review of The Seven Day Circle: The History and Meaning of the Week - Ausmus, Harry J. (The American Historical Review, 1986)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1986D315000015 tex.unique-id: [object Object]
Keywords: dept.his

Review of Explaining Religion: Criticism and Theory from Bodin to Freud - Ausmus, Harry J. (The American Historical Review, 1988)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1988R305800016 tex.unique-id: [object Object]
Keywords: dept.his

Review of Religion in the Age of Romanticism: Studies in Early Nineteenth-Century Thought - Ausmus, Harry J. (The American Historical Review, 1986)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1986F313200044 tex.unique-id: [object Object]
Keywords: dept.his